2022
DOI: 10.1002/pds.5386
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a model using routinely collected data for identifying infections following gastric, colon, and liver cancer surgeries

Abstract: Purpose Validating outcome measures is a prerequisite for using administrative databases for comparative effectiveness research. Although the Japanese Diagnosis Procedure Combination database is widely used in surgical studies, the outcome measure for postsurgical infection has not been validated. We developed a model to identify postsurgical infections using the routinely collected Diagnosis Procedure Combination data. Methods We retrospectively identified inpatients who underwent surgery for gastric, colon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Full‐text articles of 42 studies were retrieved, and six were excluded because they compared aggregate data, validated self‐report questionnaires using claims data as a reference standard, were review articles, were aimed at refining the cancer registry and not for research purposes, did not report case‐defining methods, or did not report a reference standard 12,19–23 . There were 36 eligible studies, including 29 studies 8,10,11,13,24–48 that validated administrative data using an external reference standard and seven studies 9,49–54 that validated administrative data using other data within the same database.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full‐text articles of 42 studies were retrieved, and six were excluded because they compared aggregate data, validated self‐report questionnaires using claims data as a reference standard, were review articles, were aimed at refining the cancer registry and not for research purposes, did not report case‐defining methods, or did not report a reference standard 12,19–23 . There were 36 eligible studies, including 29 studies 8,10,11,13,24–48 that validated administrative data using an external reference standard and seven studies 9,49–54 that validated administrative data using other data within the same database.…”
Section: Resultsmentioning
confidence: 99%
“…We also found studies that evaluated clinical conditions, such as gastrointestinal perforation, febrile neutropenia, and postoperative infection. 27,39,45 A study on dental claims assessed the validity of procedures, number of teeth, and time of anesthesia. 42 Another study published after our search period also validated operative information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discharge summary for each patient is coded by the attending physicians. Previous validation studies have shown that this database possesses highly accurate data on patients with esophageal cancer, 20 surgical procedures including oncologic esophagectomy, 21 comorbidities, 22 and postoperative complications 23 …”
Section: Methodsmentioning
confidence: 99%
“…Most recently, developing regression model-based event detection and validation could identify postsurgical infections from the routinely-collected DPC data in the NHO database on a cut-off score with C-statistic of 0.885, sensitivity of 92% and specificity of 72%, and on another cut-off score with sensitivity of 75% and specificity of 91%. 23 …”
Section: Data Resource Usementioning
confidence: 99%